“Little Shivta” and Other Nabataean Sites in the Shivta Hinterland - Sion, Ofer; Tepper, Yotam; Erickson-Gini, Tali (Antiguo Oriente, 2025)
The ancient village of Shivta with its well-preserved remains dating to the Byzantine period (4th-7th century CE) has garnered much attention from researchers for over a century. However, Shivta is surrounded with numerous archaeological sites and installations, some of which date to earlier centuries and others that are contemporaneous with the village. A recent survey of the Shivta hinterland has revealed numerous hewn cisterns and reservoirs, agricultural installations and towers and even small hamlets, such as small site dubbed “Little Shivta”, dated to the Roman Nabataean period (1st-3rd century CE), situated next to a massive hewn reservoir along a track south of Shivta. Here we present our findings on “Little Shivta” and another similar site, Horvat of Umm Keisume, as well as other Nabataean sites and hewn reservoirs in the Shivta hinterland.